2006
DOI: 10.1073/pnas.0604193103
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor phosphorylation and stabilization in prostate cancer by cyclin-dependent kinase 1

Abstract: Androgen receptors (ARs) are phosphorylated at multiple sites in response to ligand binding, but the kinases mediating AR phosphorylation and the importance of these kinases in AR function have not been established. Here we show that cyclin-dependent kinase 1 (Cdk1) mediates AR phosphorylation at Ser-81 and increases AR protein expression, and that Cdk1 inhibitors decrease AR Ser-81 phosphorylation, protein expression, and transcriptional activity in prostate cancer (PCa) cells. The decline in AR protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
203
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(229 citation statements)
references
References 49 publications
18
203
2
Order By: Relevance
“…Furthermore, Cyclin-dependent kinase 1 (CDK1), a 5-hmCregulated gene, is involved in AR phosphorylation (Ser81) in response to DHT stimulation 35 . The CDK1 is upregulated in BicR cells and repressed by the inhibition of miR-29a/b ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Cyclin-dependent kinase 1 (CDK1), a 5-hmCregulated gene, is involved in AR phosphorylation (Ser81) in response to DHT stimulation 35 . The CDK1 is upregulated in BicR cells and repressed by the inhibition of miR-29a/b ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also noted that phosphorylation of AR at serine 81 is promoted by miR-29 induction in HRPC cells. Phosphorylation of AR at serine 81 by CDK1 has been reported to increase AR sensitivity by promoting AR binding to specific ARBSs 35 . Thus, on the basis of the results of our clinical and biological experiments, we demonstrate the significance of TET regulation for the progression to HRPC by activating AR sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of STAT3, ZIP kinase seems to phosphorylate STAT3 directly (Sato et al, 2005). The AR is subject to multiple phosphorylations by different kinases such as PKA, PKC, MAP kinases, Akt kinase, and so on (for review, see Gioeli et al, 2002) and Cdk1/Cyclin B (Chen et al, 2006). However, although the AR has four potential phosphorylation sites for ZIPK, we did not observe a direct phosphorylation in vitro under conditions that revealed efficient phosphorylation by Cdk1/Cyclin B.…”
Section: Discussionmentioning
confidence: 99%
“…Flag-AR was isolated from transfected cells by immunoprecipitation and subjected to in vitro phosphorylation by ZIPK purified from the baculovirus expression system. As a positive control, we employed recombinant Cdk1/Cyclin B, which was shown to phosphorylate AR (Chen et al, 2006). As control substrate we included histones in the assay.…”
Section: Mapping the Interaction Domain For Ar In Zipkmentioning
confidence: 99%
“…Various studies have shown the role of glycogen synthase kinase 3b (GSK3b), stress kinase, mammalian target of rapamycin (mTOR) kinase and cyclin-dependent kinase 1 in regulating phosphorylation, stability and localization of AR (Wang et al, 2004;Cinar et al, 2005;Chen et al, 2006;Gioeli et al, 2006). Further, there are numerous studies suggesting the importance of Akt/PKB (a serine/threonine kinase) activation in AR degradation (Lin et al, 2001(Lin et al, , 2002Liao et al, 2005) as well as AR activation (Miyamoto et al, 2005;Reddy et al, 2006); though the interaction of Akt with AR largely remains unclear.…”
Section: Introductionmentioning
confidence: 99%